The Kids Are Not All Right: The Curious Case of Sapphic Censorship in City-State Singapore - Chen, Loretta (Queer Singapore : Illiberal Citizenship and Mediated Cultures, 2012)
The writer examines Singapore's Media Development Authority's censorship of representations of lesbianism in film, music video, television and theatre. She highlights the government surveillance and repression of portrayals of LGBT cultures and communities in Singapore by unpacking the ambiguities and contradictions underlying the censorship of these popular media forms. This reflects an institutional ‘inability to read lesbians’.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé